A new bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea) from Portugal with comparative remarks on the subgenus Heterodasypoda Michez - Radchenko, Vladimir G. (Zootaxa, 2017)
A new bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea, Melittidae), D. michezi Radchenko sp. nov., is described from south-western Portugal. This species belongs to the subgenus Heterodasypoda and appears very similar to D. albimana Pérez 1905, which occurs in the west Mediterranean Basin. A detailed comparative diagnosis of D. michezi with the other 3 species of the subgenus Heterodasypoda, is provided. The new species is most easily distinguishable by the widened protrusion at the apex of the 6th sternum, which is deeply emarginated apically in the form of a wide triangle. In addition, the new species differs from other described species of the subgenus by the structure of the 7th and 8th sterna, male genitalia, and relative dimensions of antennal flagellomeres.